2022
DOI: 10.3389/fmolb.2022.894207
|View full text |Cite
|
Sign up to set email alerts
|

An Altered Metabolism in Leukocytes Showing in vitro igG Memory From SARS-CoV-2-Infected Patients

Abstract: Coronavirus disease 2019 (COVID 19) is a systemic infection that exerts a significant impact on cell metabolism. In this study we performed metabolomic profiling of 41 in vitro cultures of peripheral blood mononuclear cells (PBMC), 17 of which displayed IgG memory for spike-S1 antigen 60–90 days after infection. By using mass spectrometry analysis, a significant up-regulation of S-adenosyl-Homocysteine, Sarcosine and Arginine was found in leukocytes showing IgG memory. These metabolites are known to be involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
(31 reference statements)
1
5
0
Order By: Relevance
“…Mass spectrometry measurements indicated that some altered metabolisms, such as the methionine cycle, arginine cycle, and tryptophan cycle, were impacted by COVID-19-induced changes in leukocytes. This review supports the idea that the metabolic profile changes observed in unstimulated PBMCs until after 90 days of SARS-CoV2 infection [ 20 , 22 ] could serve as a tool for evaluating disease, the modulation metabolism involved in innate and adaptive immunity, thus providing a new method for monitoring the risk of SARS-CoV2 reinfection. The analysis of these metabolites might represent a biomarker of the effective and long-standing antiviral activation of PBMCs.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Mass spectrometry measurements indicated that some altered metabolisms, such as the methionine cycle, arginine cycle, and tryptophan cycle, were impacted by COVID-19-induced changes in leukocytes. This review supports the idea that the metabolic profile changes observed in unstimulated PBMCs until after 90 days of SARS-CoV2 infection [ 20 , 22 ] could serve as a tool for evaluating disease, the modulation metabolism involved in innate and adaptive immunity, thus providing a new method for monitoring the risk of SARS-CoV2 reinfection. The analysis of these metabolites might represent a biomarker of the effective and long-standing antiviral activation of PBMCs.…”
Section: Discussionsupporting
confidence: 73%
“…In this regard, accurate tests that can identify the SARS-CoV2 virus and monitor antiviral antibodies are essential for identifying those who have had an immune response to the virus, aiding in virus management and surveillance and combating the COVID-19 pandemic [ 19 ]. Furthermore, understanding the molecular mechanism involved in physiological recovery from viral infections and immune activities in leukocytes [ 20 ] became crucial for knowing the antibody-mediated immune response to SARS-CoV2.…”
Section: Metabolic Rewiring In Sars-cov2-infected Patientsmentioning
confidence: 99%
See 3 more Smart Citations